Simply divine : a guide to easy, elegant, and affordable entertaining - Vanderpump, Lisa (Running Press, 2011)
Presents a collection of more than seventy-five party recipes along with advice on entertaining from the English restaurant owner who is one of the stars of the television program "The Real Housewives of Beverly Hills."